The role of external beam radiotherapy in the treatment of hepatocellular carcinoma - Thonglert, Kanokphorn (Journal of Thai Association of Radiation Oncology, 2022)
External beam radiotherapy (EBRT) previously played a minor role in the treatment of patients with hepatocellular carcinoma (HCC). While HCC is responsive to radiation, the normal liver is extremely sensitive. As a result, a high rate of radiation-induced liver disease was observed. Nowadays, radiation technology has made significant advancements. EBRT is being used in an increasing number of settings, including definitive, adjuvant, salvage, preoperative (including bridge to transplantation), and palliative EBRT for symptomatic primary lesions. The regimen and technique of dose fractionation should be determined by the size and location of the tumor, as well as the underlying liver function. The goal of treatment is to deliver moderate dose escalation radiotherapy while minimizing liver doses in order to improve tumor control while minimizing the risk of liver toxicity in HCC patients.